Morale in the market - Tone Ognedal (University of Oslo, Department of Economics, 2014)
There is a growing interest in morale as a potential substitute for sanctions, encouraged by exerimental evidence that people's morale affect their economic decisions. I show that while morale may be a substitute for sanctions for each citizen, it is not a substitute in the market. In a model where employed and self-employed differ in their opportunities for tax evasion, I demonstrate that a higher fraction of tax compliant citizens may reduce social surplus and tax revenues. In contrast to sanctions, morale usually differ between individuals and this distorts the ranking of costs among sellers and willingness to pay among consumer. Tax evading sellers crowd out tax compliant sellers with higher productivity. Tax evading buyers crowd out tax compliant buyers with higher willingness to pay. As a result, improved tax morale may lead to less efficient production and exchange. Experiments show how sanctions crowd out morale in some settings. My paper points to the opposite problem in markets: Low sanctions may crowd out morale. While the paper explores the effects of tax morale only, the results apply to a wide range of areas where morale matters for peoples choices in he market, such as environmental and safety regulation.
Keywords: H26; K42; D01; 330; Tax morale; Tax evasion; Norms; Sanctions